Antineutrophil Cytoplasmic Antibody (ANCA)-associated vasculitis following COVID-19 BBIBP-CorV vaccine: A case report - Parisa Javadian; Negin Fadaei-Tirani; Zainab Amoosoltani-Forooshani; Vahid Reisi-Vanani; Mina Borran (Clinical Infection in Practice, 2024)
COVID-19 and its vaccination could initiate autoimmunity including ANCA-associated vasculitis that could mimic COVID-19 infection symptoms. This misdiagnosis could increase the morbidity of AAV. Herein a case of AAV post-BBIBP-CorV (Sinopharm) COVID-19 vaccine was reported. A 32-years-old woman was admitted with flu-like symptoms, flank pain, hemoptysis, hematuria, and oliguria following the second dose of BBIBP-CorV vaccination. Due to her severe clinical course, she needed ICU care while plasma exchange, renal replacement therapy, corticosteroid pulse, and tocilizumab were the primary therapies that improved her symptoms. After more evaluation, she was diagnosed with AAV, and conservative therapy was initiated. Her pulmonary condition and renal function were resolved gradually. Reports of post-COVID-19 vaccination raised the need for assessment of the immune response caused by these vaccines. Physicians also should be aware of the misdiagnosis of AAV and other infectious diseases.